"Be Not Afeard, the Isle Is Full of Noises": Expanding Youths' Aspirations Through Shakespeare and Musical Productions in the Marshall Islands. Issue 3 (18th March 2022) - Garrod, Andrew; Nalani, Andrew
Abstract: In this article, we discuss theater productions we mounted in the Marshall Islands as a case example of how the theatrical process, shaped by "polycultural" inclinations, contributes to the personal development of youth in the Marshall Islands. We contextualize and detail a unique theatrical process that has potential for fostering youths' personal and collective competencies in a troubled context. By taking on another character, the youth actors extend their perceptions of who they are and what they are capable of and, in the process, they reinterpret the text that is their own life.